O panorama da física na Colômbia: implantação e desenvolvimento: um aporte ao sistema nacional de informação - Parra Santos, Alejandro (1977)
Description of the National Information System of Colombia since its origin until the present situation, indicating its objective, structure, mode of operation, programme of activities and steps of establishment. As a contribution to the SNI documentation programme it was done a study on the establishment and development of Physics in Colombia. It is presented a systematic description of institutions of higher education having Physics as part of its programmes, human resources involved – degree activities and field of interest, research institutions, supporting organisations and scientific literature produced in Colombia.